2018
DOI: 10.5267/j.msl.2018.4.027
|View full text |Cite
|
Sign up to set email alerts
|

The impact of word of mouth and university reputation on student decision to study at university

Abstract: This study aims to analyze the influence of word of mouth and university reputation on student decision to study at faculty of economics at the Universitas Islam Sumatera Utara (UISU), Indonesia. This research uses quantitative approach with explanatory research type. The sample size includes all 177 new university students of academic year 2015-2016 and processed statistically with multiple linier regression method. Results show that word of mouth does not positively influence on students' decision to study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 29 publications
1
23
0
6
Order By: Relevance
“…From several previous studies it was concluded that the main reason for choosing a particular university in Indonesia was affordable education costs (Handayani, 2007;Tambunan, 2010;Handayani, 2007;Tambunan, 2010;Suryani & Ginting, 2013;Khoiriyah et al, 2013;Artini et al, 2014;Meilyaningsih & Sisilia, 2015. Besides WOM because it is a marketing effort that encourages people or prospective students to discuss, promote, recommend certain universities to prospective other students (Tambunan, 2010;(Tambunan, 2010;Suryani & Ginting, 2013;Khoiriyah et al, 2013;Widowati & Surjawati, 2015;Meilyaningsih & Sisilia, 2015;Journal of International Business, Economics andEntrepreneurship ISSN :2550-1429 Volume 4, (1) June 2019 Harahap, Hurriyati, Gaffar, Wibowo, & Amanah, 2017a;Harahap et al, 2018). The university's reputation is also a consideration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From several previous studies it was concluded that the main reason for choosing a particular university in Indonesia was affordable education costs (Handayani, 2007;Tambunan, 2010;Handayani, 2007;Tambunan, 2010;Suryani & Ginting, 2013;Khoiriyah et al, 2013;Artini et al, 2014;Meilyaningsih & Sisilia, 2015. Besides WOM because it is a marketing effort that encourages people or prospective students to discuss, promote, recommend certain universities to prospective other students (Tambunan, 2010;(Tambunan, 2010;Suryani & Ginting, 2013;Khoiriyah et al, 2013;Widowati & Surjawati, 2015;Meilyaningsih & Sisilia, 2015;Journal of International Business, Economics andEntrepreneurship ISSN :2550-1429 Volume 4, (1) June 2019 Harahap, Hurriyati, Gaffar, Wibowo, & Amanah, 2017a;Harahap et al, 2018). The university's reputation is also a consideration.…”
Section: Discussionmentioning
confidence: 99%
“…If reality does not meet expectations, success will be uncertain. The act of choosing a university has many dimensions and impacts which are part of the resolution effort and part of the decision making process (Harahap, Hurriyati, Gaffar, & Amanah, 2018).…”
Section: Student Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many researchers have demonstrated that marketing plays an important role in student enrollment, and these researchers have tried to exemplify how students choose HE (Tapp, Hicks, & Stone, 2004;Cubillo, Sanchez, & Cervin, 2006). But this is not an easy matter for every university to develop higher education institutions in Indonesia, given the tighter competition with other universities (Harahap, Hurriyati, Gaffar, & Amanah, 2018). Studies that have been documented in some literature that focus on higher education (HE), there are many factors that influence students' decisions to choose a particular college, namely the cost of education (Xiaoping, 2002), and perceptions about the quality of educational programs (Zain & Nik-Yacob, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The act of selecting higher education has many dimensions and impacts, namely part of the resolution effort and part of the decision-making process. Intense competition makes every university realize the need to fully exploit its assets to maximize performance and to develop competitive advantage (Harahap, Hurriyati, Gaffar, & Amanah, 2018).…”
Section: Introductionmentioning
confidence: 99%